Pertumbuhan Vegetatif dan Generatif Jambu Air (Syzygium samarangense (Blume) Merr. & Perry) Varietas Deli Hijau dengan Perlakuan ZPT dan Media Tanam - Victor Hevit Tarigan; Chairani Hanum; Revandi I M Damanik (Jurnal Agroekoteknologi, 2015)
The objective of research was to study effect of planting media, paclobutrazol and gibberellin acid on vegetative and generative growth of Deli Hijau rose apple. The research has been conducted at Desa Sei Remban, Kecamatan Binjai Utara, Binjai, Sumatera Utara from June to November 2014, using factorial randomized block design with three factors. The first factor were planting media (chicken and cow manure),the second factor were paclobutrazol (0 and 5 ml) and the third factor were GA3 (0 and 75 ppm). The result showed that paclobutrazol decrease of plant height (17.3%), stem diameter (10.28%), to accelarate bud initiaton (93.69%), to increase bud branch number (75.68%), flower opening stage (86.47%), and bud number per branch (74.82%). There were not different response vegetative and generative growth of Deli Hijau rose apple with manure and GA3 traetment. The highest leaf area of Deli Hijau rose apple on using chicken manure with application GA3.Keywords: deli hijau, gibberellin acid, paclobutrazol, planting media, rose apple